Into The Land of Nod Drugs Used During Anesthesia in Day Surgery - Phillips, Marjorie (Operating Room Nurses Association of Canada Journal, 1994)
This paper lists and describes some of the drugs used during anesthesia in a Day Surgery Operating Room. The classification, action and implications of these drugs are addressed. The discussion is presented under the drug classes as Narcotic Analgesics/Opioids Antagonists, Opiate Antagonists, Induction Agents, Muscle Relaxants/Neuromuscular Blocking Agents, InhalationAnesthetics, Cholinesterase Inhibitors Anticholinesterases/Parasymphathomimetics, Anticholinergics/Antimuscarinicsl Parasympatholytics, and Antiemitics.